Effect of strength training on running economy in endurance runners: a literature review - Bernardo Silva, João Paulo (2024)
BACKGROUND: Street running is an easy activity to perform, just like practice, running events have grown in the last decade, an event that quickly makes runners migrate from recreational to competitive practice and seek ways to increase performance. Running economy (RE) has a direct relationship with the VO2max required at a given submaximal intensity, evidenced by scientific literature as the best predictor of the athlete’s performance. Strength training (TF) supplementary to running training has been shown to be an excellent strategy for improving EC. There are several TF methods and programs related to the advantage provided by improving EC. OBJECTIVE: To verify which are the main TF methods used to enhance EC. METHODS: The following keywords were analyzed in the PubMed database: economic running, strength training, runners. RESULTS: For this analysis, nineteen studies were examined. Recreational corridors accounted for more than 50% of the total samples. CE had a significant improvement in 12 studies, while 7 showed no significant improvements in their interventions. Maximum TF was researched and was shown to be the most beneficial for CE. The weekly intervention sessions in the studies were: less than two, two and three sessions, while the intervention period varied between 4 and 40 weeks. CONCLUSION: TF as a strategy to supplement long-distance running proved to be effective in saving running. Various methods, exercises and intervention periods were investigated. A period of 8 to 12 weeks with 2 or 3 weekly sessions demonstrated significant gains in EC.